A study on the treasury bill interest rates and selected variables vis-a-vis the stock market composite indexes as a tool in financial investment decisions - Camacho, Daniel D. (Animo Repository, 1992)
The main objective of this study is to determine whether the 91-day T-bill rate has a direct or inverse relationship with the Manila and Makati Stock Exchanges and to what degree. Moreover, it seeks to discover the other variables that affect the stock market to explain this relationship. The period included is yearly, from 1987-1991. As numerous authors have written, the theory is that the interest rate is inversely related to the stock market. The outcome of this study will show whether or not this is true in the Philippine situation. At the same time, the results may guide investors and investment managers when making financial investment decisions. Monthly data were used for the variables and were regressed to determine the correlation between the dependent and independent variables. A linear regression was done using T-bills alone, afterwards a multiple regression was done considering the other variables. These were arrived at based on theories, logical reasoning and interviews of industry experts. A graphical depiction follows to better show a trend of the movements of the variables. The study shows that Treasury Bills alone are not sufficient to explain the movement of the stock market because of several reasons. The other variables, both quantitative and qualitative, also explain the reason for the relationship between T-bills and the stock market. It is recommended that structural reforms be adopted in the financial market, particularly the capital market, to ensure efficient allocation of resources. Furthermore, studies should be made considering other variables and investment alternatives to determine the factors that affect the stock market.